Fresnel Equations and Snell's Law

  • #1
says
594
12

Homework Statement


From the Fresnel equations and Snell’s Law, prove that, when θ = θB where tanθB = nt/ni, (θB is the Brewster angle); (a) Reflection coefficient = 0 , and (b) transmission coefficient = n/n’

Homework Equations


reflection coefficient = (ntcosθi - nicosθt) / (ntcosθi + nicosθt)

transmission coefficient = (2nicosθi) / (ntcosθi+nicosθt)

Snell's Law : nisinθi = ntsinθt

Brewster's Angle: θi + θt = 90°

The Attempt at a Solution



I know that for Brewster's Angle θi + θt = 90°

Part a) is basically asking to derive the current version of the reflection coefficient, into it's more known tangent version:

tan(θi - θt) / tan(θi + θt)

For Brewster's Angle tan(θi + θt) = tan(90°) = 0

So reflection coefficient will equal 0.

Rearranging Snell's Law: ni= ntsinθt / sinθi

Subbing ni into the reflection coefficient and multiplying both numerator and denominator by sinθi / nt gives:

(sinθtcosθt - sinθicosθi) / (sinθtcosθt + sinθicosθi)

I don't know how to get from there to tan though. Any help would be much appreciated.
 

Answers and Replies

  • #2
nrqed
Science Advisor
Homework Helper
Gold Member
3,764
295

Homework Statement


From the Fresnel equations and Snell’s Law, prove that, when θ = θB where tanθB = nt/ni, (θB is the Brewster angle); (a) Reflection coefficient = 0 , and (b) transmission coefficient = n/n’

Homework Equations


reflection coefficient = (ntcosθi - nicosθt) / (ntcosθi + nicosθt)

transmission coefficient = (2nicosθi) / (ntcosθi+nicosθt)

Snell's Law : nisinθi = ntsinθt

Brewster's Angle: θi + θt = 90°

The Attempt at a Solution



I know that for Brewster's Angle θi + θt = 90°

Part a) is basically asking to derive the current version of the reflection coefficient, into it's more known tangent version:

tan(θi - θt) / tan(θi + θt)

For Brewster's Angle tan(θi + θt) = tan(90°) = 0

So reflection coefficient will equal 0.

Rearranging Snell's Law: ni= ntsinθt / sinθi

Subbing ni into the reflection coefficient and multiplying both numerator and denominator by sinθi / nt gives:

(sinθtcosθt - sinθicosθi) / (sinθtcosθt + sinθicosθi)

I don't know how to get from there to tan though. Any help would be much appreciated.
Wait... for part b) they are asking to find the transmission coefficient, right? Are you calculating the reflection coefficient??
 
  • #3
says
594
12
Yes, for part a) I need to derive the reflection coefficient and part b) the transmission coefficient
 
  • #4
nrqed
Science Advisor
Homework Helper
Gold Member
3,764
295
Yes, for part a) I need to derive the reflection coefficient and part b) the transmission coefficient
Ah, I thought you had started part b). Ok.

Note that it is not true that tan(90) = 0.


You have to use trig identities for the product of sin(A) cos(A)
 
  • #5
says
594
12
something like ... sin(A)cos(A) = 1/2(2sinAcosA) = 1/2(sin2A) = sin2A/2
 
  • #6
says
594
12
or 2sinAcosA = sin2A
 
  • #7
nrqed
Science Advisor
Homework Helper
Gold Member
3,764
295
or 2sinAcosA = sin2A
Right. And then use the identity for sin(A) + sin(B) and so on.
 
  • #8
says
594
12
Right. And then use the identity for sin(A) + sin(B) and so on.

I don't follow why I need to use sin(A) + sin(B) identity
 
  • #9
nrqed
Science Advisor
Homework Helper
Gold Member
3,764
295
I don't follow why I need to use sin(A) + sin(B) identity
Write the next few steps. You will encounter this type of terms
 
  • #10
says
594
12
ok, so I think I have it. I've replaced most of the terms with A and B for easier writing / reading at this point.

2sinAcosA = sin2A

(2sinAcosA - 2sinBcosB) / (2sinAcosA + 2sinBcosB)

= sin2A - sin2B / sin2A + sin2B

= 2sin(A-B)cos(A+B) / 2sin(A+B)cos(A-B)

At Brewster's Angle, A+B = 90°, therefore

= 2sin(A-B)cos(90) / 2sin(90)cos(A-B)

cos(90°) = 0, therefore

Reflection coefficient = 0 at Brewster's Angle
 
  • #11
nrqed
Science Advisor
Homework Helper
Gold Member
3,764
295
ok, so I think I have it. I've replaced most of the terms with A and B for easier writing / reading at this point.

2sinAcosA = sin2A

(2sinAcosA - 2sinBcosB) / (2sinAcosA + 2sinBcosB)

= sin2A - sin2B / sin2A + sin2B

= 2sin(A-B)cos(A+B) / 2sin(A+B)cos(A-B)

At Brewster's Angle, A+B = 90°, therefore

= 2sin(A-B)cos(90) / 2sin(90)cos(A-B)

cos(90°) = 0, therefore

Reflection coefficient = 0 at Brewster's Angle
good job :-)
 
  • #12
says
594
12
I'm not sure how to get started with the transmission coefficient. There are so many substitutions and trig identities to try...
 
  • #13
says
594
12
At brewster's angle nisinθi = ntcosθi

2nicosθi / ntcosθi+nicosθt

= 2nicosθi/nisinθi+nicosθt

= 2cosθi/sinθi+cosθt

I'm kind of stuck here though...
 
  • #14
says
594
12
ok, I think I've figured it out using Snell's Law:

nisinθi=ntsinθt

nisinθi=ntsin(90-θB

nisinθi=ntcosθB

OR

nisinθi=ntcosθi

2nicosθi / ntcosθi+nicosθt

subbing in the relation: nisinθi=ntcosθi

2nicosθi / nisinθi+nicosθt

Multiply numerator and denominator by 1/ni

2cosθi / sinθi+cosθt

subbing in relation: cosθt = sinθi

cosθt = sin(90-θt) = sinθi

2cosθi / sinθi+sinθi

2cosθi / 2sinθi

= ni / nt
 

Suggested for: Fresnel Equations and Snell's Law

  • Last Post
Replies
7
Views
683
  • Last Post
Replies
7
Views
1K
  • Last Post
Replies
3
Views
2K
  • Last Post
Replies
3
Views
1K
  • Last Post
Replies
2
Views
7K
Replies
1
Views
383
  • Last Post
Replies
8
Views
21K
  • Last Post
Replies
18
Views
1K
  • Last Post
Replies
3
Views
2K
  • Last Post
Replies
0
Views
4K
Top